Targeted values: The relevance of classical Chinese philosophy for illegal wildlife demand reduction campaigns. Issue 4 (4th August 2020) - Thomas‐Walters, Laura; Cheung, Hubert; Lee, Tien Ming; Wan, Anita Kar Yan; Wang, Yifu
Abstract: The illegal wildlife trade is a global conservation priority, prompting a rise in interventions aimed at reducing the demand for wildlife products. Research shows that designing campaigns to target the values held by a specific audience is an effective way to alter their behaviour. However, many demand reduction campaigns are grounded in the perspective of Western morality. This is problematic when the recipients of these campaigns frequently reside in East Asia, where they are exposed to the historical and cultural praxis of Confucianism and Daoism. This paper examines some of the central concepts of classical Chinese philosophy to see how they could be used by practitioners to design effective behaviour change campaigns in the future. Acknowledging that the East Asian cultural sphere has a long history of consumptive wildlife use, reflecting an instrumentalist and anthropocentric approach to wildlife, we still find potential for appealing to a relational ethic. There is a fundamental metaphysics that all of nature is unified, interconnected and interpenetrating. Qi is the vital force of the universe that links inorganic, organic and human life‐forms, creating the basis for a profound reciprocity between humans and the natural world. We also consider some of the key virtues in Chinese philosophy, and how they could be interpreted through the lens of demand reduction for illegal wildlife products. This includes li, ritual propriety, and ren, the inner moral force which keeps us in balance. Finally, we cover influential scriptures, identifying many historical verses that are relevant to modern conservationists. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. 摘要: 非法野生动植物贸易是全球保护工作的重点，促使了针对减少野生动物产品需求的干预活动的增加。研究表明，设计以特定受众持有的价值观为目标的活动是改变受众行为的有效方法。然而，许多减少需求的活动都基于西方的道德观。矛盾在于这些活动的受众经常为东亚居民，接受儒家和道教的历史和文化实践。 本文考察了中国古典哲学的一些核心概念来看从业者如何利用这些概念设计未来有效的行为改变运动。即使认识到东亚文化领域具有悠久的使用野生动物制品的历史，反映出对野生动物有着工具主义和以人为中心的视角，我们仍然发现有潜力的关系伦理学理论。其中一个基本的形而上学理论即万物是统一的，交互的，相互渗透的。 气 是宇宙的生命力，将一切无机的、有机的与人类联系起来，这为人类与自然世界之间的互惠关系奠定了基础。 我们还考虑了中国哲学中的一些重要美德，以及如何从减少非法野生动物产品需求的角度来解释它们，包括 礼 （仪式礼节）和 仁 （保持我们平衡的内在道德力量）。最后，我们引用了几篇中国传统经文，找出许多与现代环保主义者相关的古代哲学观点。